Badania nad Nowym Testamentem w „Collectanea Theologica” 1920-2020 - Adamczewski, Bartosz (Collectanea Theologica, 2020)
The New Testament articles published in the Polish theological journal “Collectanea Theologica” initially (1920-1965) had significant apologetic characteristics. After the Second Vatican Council (1966-1989), they became more pastorally oriented. Especially in the years 1990-2006, many articles were devoted to the relationship between Christianity and Judaism. Since 2007, the problem of the reception of the Old Testament in the New Testament has become much more prominent. In general, the articles related to the New Testament bear witness to the strong ties of Polish biblical scholarship with the Vatican documents concerning Scripture as well as the exegetical methods elaborated in the pontifical universities and institutes in Rome. On the other hand, the heritage of German biblical scholarship is treated in the New Testament articles published in “Collectanea Theologica” with greater mistrust and criticism.